Combined transcriptomic and proteomic analysis of flubendiamide resistance in Plutella xylostella. Issue 10 (15th August 2020) - Li, Jing‐Jing; Jin, Ming‐Hui; Wang, Nian‐Meng; Yu, Qi‐Tong; Shang, Ze‐Yu; Xue, Chao‐Bin
Abstract: Diamondback moth (DBM), Plutella xylostella, is an important pest of crucifers worldwide. The extensive use of diamide insecticides has led to DBM resistance in the world, and this presents a serious threat to vegetable production. In the present study, transcriptomic and proteomic analyses were combined to investigate the potential flubendiamide‐resistance mechanism in DBM. The lab‐selected (Rh ) and field‐collected (Rb ) flubendiamide‐resistant lines of P. xylostella with resistance ratios of 1889.92‐fold and 1250.97‐fold, respectively, were used, as well as a lab‐reared flubendiamide‐susceptible line (S). Compared with the S group, the transcriptomic analysis revealed 151 upregulated and 287 downregulated gene messengers in the Rh group and 432 upregulated and 565 downregulated gene messengers in the Rb group. The most frequently enriched pathways of differentially expressed genes (DEGs) were mainly involved in metabolic pathways. Metabolism related genes, including two P450, two ABC transporters, and three trypsins, were upregulated in the Rh line. Additionally, some P450 genes, trypsin, juvenile hormone (JH), and mucin genes were also upregulated in the Rb line. In proteomic analysis comparisons with the S group, there were 78 upregulated and 90 downregulated proteins in the Rh group and 221 upregulated and 155 downregulated proteins in the Rb group. Further analyses found that three CYP and 11 CYP proteins were over‐expressed in Rh and Rb lines, respectively. Four glutathione S‐transferase (GST) and four UGTs were over‐expressed in Rb line. So, we deduced that the detoxification metabolism may be the main mechanism of flubendiamide resistance in P. xylostella .